2019
DOI: 10.1108/ijcthr-07-2018-0090
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of cultural events organized by hotels

Abstract: Purpose This paper aims to determine how important cultural events organized by hotels are when guests select the establishment, determine the most influential source to attract customers to the hotels’ cultural events and measure their ability to meet guests’ expectations. Design/methodology/approach A qualitative exploratory methodology was adopted. Data collection was performed through voluntary and non-probabilistic face-to-face interviews to 2,229 guests and six directors from eight hotels that organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A significant number of studies have shown that regularly planned and executed ethno-cultural events and festivals are detrimental to tourism survival and growth. Reference [37] studied the reinvention of local, regional, and international games and festivals in post-Apartheid South Africa have positively contributed to the economy of the country. Ethno-cultural events and festivals in the study have been suggested to be managed by the communities in collaboration with tourism practitioners and organizers, but they can also be organized by hotels or hotel associations.…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of studies have shown that regularly planned and executed ethno-cultural events and festivals are detrimental to tourism survival and growth. Reference [37] studied the reinvention of local, regional, and international games and festivals in post-Apartheid South Africa have positively contributed to the economy of the country. Ethno-cultural events and festivals in the study have been suggested to be managed by the communities in collaboration with tourism practitioners and organizers, but they can also be organized by hotels or hotel associations.…”
Section: Discussionmentioning
confidence: 99%
“…This type of capital must be properly managed and maintained with regard to its potential for SD [56]. Freitas and Correia [60] suggested that cultural events were one of the most important components in hospitality attractiveness. Their purpose is to attract a large number of tourists, and therefore hotels that organize such events benefit in a variety of ways, such as through image recognition, strengthening of brand positioning, and simply attracting customers.…”
Section: Cultural Capitalmentioning
confidence: 99%
“…The most important benefits of cultural events are the ability to attract customers' attention and act as incentives, thereby offsetting the problem of seasonality faced by the hotel industry. When guests participate in these activities and doing so meets their expectations, this helps to improve the overall positive satisfaction they have with the hotel [60].…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%
See 2 more Smart Citations